A modelling-based assessment of EU supported natural gas projects of common interest. (July 2022) - Selei, Adrienn; Takácsné Tóth, Borbála
Abstract: Between 2013 and 2020 the EU set up a complex institutional system to select and support the implementation of energy infrastructure projects that are of European interest (PCIs). EUR 1.4 billion EU support was awarded to 16 natural gas projects between 2014 and 2019, most of them are still under construction. With the decarbonization agenda emerging, fossil investments have a limited lifetime to recover their investment. To assess the net socio-economic benefits of the gas PCI projects a modelling-based cost benefit analysis was applied. Results revealed that the cross-border projects that were implemented so far have a joint socio-economic benefit/cost ratio (B/C) above 1 even in the most conservative scenario setups. The ones with a final investment decision would need to face a high gas price environment in the future to push the B/C above 1, which is the reality since 2021. The other projects on the full EU list of PCIs are not beneficial as a single group, as they serve similar needs. Some individual non-FID projects are though promising. Highlights: CEF support of gas PCIs already in place was socio economic beneficial. FID gas projects will be useful in a gas price environment higher than in 2020. Uncertainty about future gas demand is the highest risk for non-FID gas projects. Competing gas projects on the PCI list will not all materialize. The LNG projects perform well in most of the scenarios.